Achieving Sustainable, Community-Based Health in Detroit Through Adaptation of the UNSDGs - Alexander Plum; Linda Kaljee (Ubiquity Press, 2017)
Background In 2012, the Rio+20 meeting initiated the concept of the Sustainable Development Goals (SDGs) as a continuation of the Millennium Development Goals. The resulting document "The Future We Want" is best conceived as a roadmap toward poverty eradication and sustainable development. Although the SDGs were developed for low- and middle-income countries, many of these same issues face low-resource cities and communities in higher-income countries. Objectives The aim of this study was to use the SDGs as a platform to develop health-related goals for the city of Detroit. Methods A 1-day workshop was convened in October 2015 including 55 representatives from government, academia, and community- and faith-based organizations. Four health-related SDGs were discussed: food security (SDG2); ensuring healthy lives at all ages (SDG3); access to potable water (SDG6); and making cities inclusive, safe, resilient, and sustainable living environments (SDG11). Workshop attendees broke into 4 groups to determine how the SDG targets for these 4 goals could be adapted for Detroit. At the end of the day, each group presented its decisions to the larger group. Findings Workshop participants expressed that the SDGs empower local communities to respond to their unique health challenges and to see themselves as part of a larger more global conversation about development and sustainability. Participants suggested that inclusive and participatory means of decision making were a significant component of the SDGs and that such a process is the direction needed to make community-focused changes in Detroit. Additionally, shortly after the workshop, a roundtable of participants representing 5 community partners began to meet monthly and has become an advocacy group for public health and addressing the city-order water shutoffs in neighborhoods throughout Detroit. Conclusions For participants and organizers, the workshop reinforced the hypothesis that the SDGs are relevant to Detroit and other low-resource cities in the United States.